Analysis of urban accessibility as a condition of social inequality in peripheral human settlements in a medium city. Case study: Culiacan, Mexico.: : Culiacan, Mexico. (REVISTA NODO, 2015)
In this paper, the methodology and the main results of the analysis of urban accessibility in peripheral settlements are presented. It is hypothesized that the socio-spatial structure of human settlements on the periphery of a medium city, as is the case of Culiacan, is the main factor that generates conditions of inequality and social inequity in urban accessibility for residents of this sector of the city. The importance of aspects such as location, travel time, cost, and transport in a monocentric city is revealed. The methodology developed is both qualitative and quantitative, using the City of Culiacan, Mexico as a case study for instrumental purposes.
Keywords: Transport; mobility; medium city